CERAI DENGAN ALASAN SALAH SATU PASANGAN MEMILIH CHILDFREE PERSPEKTIF KOMPILASI HUKUM ISLAM - Syafiq Riza Hasan; Farchan Mu'aziz; Teguh Dwi Cahyadi (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
ABSTRACT Islam is a religion that encompasses all aspects of life. One of them is that Islam pays attention to the continuity of human life through marriage. However, in reality, married life is not as smooth as imagined. Many married couples face disharmony in their marriage, which often leads to divorce. Divorce can occur for various reasons. As time progresses, more complex problems arise, one of which is known as